Exosomes from human adipose‐derived stem cells promote sciatic nerve regeneration via optimizing Schwann cell function. Issue 12 (23rd May 2019) - Chen, Jing; Ren, Sen; Duscher, Dominik; Kang, Yu; Liu, Yutian; Wang, Cheng; Yuan, Meng; Guo, Guojun; Xiong, Hewei; Zhan, Peng; Wang, Yang; Machens, Hans‐Günther; et al.
Abstract: Human adipose‐derived stem cells (ASCs) have a potential for the treatment of peripheral nerve injury. Recent studies demonstrated that stem cells can mediate therapeutic effect by secreting exosomes. We aimed to investigate the effect of human ASCs derived exosomes (ASC‐Exos) on peripheral nerve regeneration in vitro and in vivo. Our results showed after being internalized by Schwann cells (SCs), ASC‐Exos significantly promoted SC proliferation, migration, myelination, and secretion of neurotrophic factors by upregulating corresponding genes in vitro. We next evaluated the efficacy of ASC‐Exo therapy in a rat sciatic nerve transection model with a 10‐mm gap. Axon regeneration, myelination, and restoration of denervation muscle atrophy in ASC‐Exos treated group was significantly improved compared to vehicle control. This study demonstrates that ASC‐Exos effectively promote peripheral nerve regeneration via optimizing SC function and thereby represent a novel therapeutic strategy for regenerative medicine and nerve tissue engineering. Abstract : This study demonstrates that ASC‐Exos effectively promote peripheral nerve regeneration via optimizing Schwann cell function and thereby represent a novel therapeutic strategy for regenerative medicine and nerve tissue engineering.